2014
DOI: 10.3343/alm.2014.34.5.354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Optimal Neutrophil Gelatinase-Associated Lipocalin Value as a Screening Biomarker for Urinary Tract Infections in Children

Abstract: BackgroundNeutrophil gelatinase-associated lipocalin (NGAL) is a promising biomarker in the detection of kidney injury. Early diagnosis of urinary tract infection (UTI), one of the most common infections in children, is important in order to avert long-term consequences. We assessed whether serum NGAL (sNGAL) or urine NGAL (uNGAL) would be reliable markers of UTI and evaluated the appropriate diagnostic cutoff value for the screening of UTI in children.MethodsA total of 812 urine specimens and 323 serum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 18 publications
0
29
0
2
Order By: Relevance
“…Following transurethral inoculation with strains of uropathogenic E. coli, NGAL knock-out mice have a higher bacterial burden for a significantly longer period of time compared to wild type mice, highlighting the importance of NGAL in local bacteriostasis [7]. However, there are conflicting reports of the utility of NGAL as a marker of UTI within the literature, as some studies have not shown a difference in uNGAL levels between children with UTI and controls [8]. This may be related in part to the specificity of uNGAL for gram-negative bacteriuria, or due to misclassification bias given that the UTI group in the study in which no difference was reported included patients with asymptomatic bacteriuria in the UTI group [8].…”
Section: Ngal and Urinary Tract Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following transurethral inoculation with strains of uropathogenic E. coli, NGAL knock-out mice have a higher bacterial burden for a significantly longer period of time compared to wild type mice, highlighting the importance of NGAL in local bacteriostasis [7]. However, there are conflicting reports of the utility of NGAL as a marker of UTI within the literature, as some studies have not shown a difference in uNGAL levels between children with UTI and controls [8]. This may be related in part to the specificity of uNGAL for gram-negative bacteriuria, or due to misclassification bias given that the UTI group in the study in which no difference was reported included patients with asymptomatic bacteriuria in the UTI group [8].…”
Section: Ngal and Urinary Tract Infectionsmentioning
confidence: 99%
“…However, there are conflicting reports of the utility of NGAL as a marker of UTI within the literature, as some studies have not shown a difference in uNGAL levels between children with UTI and controls [8]. This may be related in part to the specificity of uNGAL for gram-negative bacteriuria, or due to misclassification bias given that the UTI group in the study in which no difference was reported included patients with asymptomatic bacteriuria in the UTI group [8]. In the earlier cited study by Yilmaz et al [6], all of the patients had E. coli as the causative agent of their UTIs, whereas bacteriology data were not reported in the latter study by Kim et al [8], and may potentially confound the results.…”
Section: Ngal and Urinary Tract Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, novel biomarkers are emerging as alternative tools in the diagnosis of UTI (6)(7)(8)(9)(10)(11)(12)(13), and as predictors of its complications such as vesico-ureteric reflux (VUR) (14)(15)(16)(17)(18) as well as renal parenchymal injury (19)(20)(21)(22). Reports also show that febrile UTI in children activate an interleukin 6 (IL-6) and interleukin 8 (IL-8) responses, thus adding the estimation of these cytokines in the diagnostic trajectory of the disease (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…22 Several novel biomarkers have recently been documented as diagnostic and prognostic tools in diseases such as pediatric acute kidney injury, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] and urinary tract infection. [37][38][39][40][41][42][43] Similarly, the utility of biomarkers in childhood idiopathic nephrotic syndrome has been reported; [12][13][14][15][16][17][18][19][20] their application constitutes a noninvasive approach in diagnostic nephrology, as they can be used as diagnostic and prognostic tools in idiopathic nephrotic syndrome, as well as discriminatory tools in distinguishing SRNS from SSNS (Table 1).…”
Section: The Diagnostic Prognostic and Discriminatory Roles Of Biommentioning
confidence: 99%